1993
DOI: 10.1159/000468686
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Multicatalytic Proteinase Complex by Lipids, Interconversion and Proteolytic Processing

Abstract: In studying the modulation of multicatalytic proteinase (MCP), we have focused on three main aspects; (1) modulation of the activity of the MCP complex by lipids, showing that cardiolipin, sulfatides and gangliosides are potent activators of the enzymatic activity of the complex; (2) modulation by interconversion of MCP subunits, showing that casein kinase II is able to phosphorylate the C8 (this subunit is also be main in vivo phosphorylated subunit) and C9 subunits of the complex in vitro and that a 26-kD su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Except for this exchange no other consistent alterations in the two-dimensional pattern of the 20 S proteasome were noted. The significant acidic shift of the subunit C8 (30 kDa, basic of delta) in the double transfectant might be due to phosphorylation (45), but as it was not observed in a second preparation we did not further investigate this issue. The size and isoelectric point of the overexpressed LMP2 and LMP7 proteins in single and double transfectants are identical to those of the endogenously expressed proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Except for this exchange no other consistent alterations in the two-dimensional pattern of the 20 S proteasome were noted. The significant acidic shift of the subunit C8 (30 kDa, basic of delta) in the double transfectant might be due to phosphorylation (45), but as it was not observed in a second preparation we did not further investigate this issue. The size and isoelectric point of the overexpressed LMP2 and LMP7 proteins in single and double transfectants are identical to those of the endogenously expressed proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suspect that an enrichment of the microsomal fraction with other membranes resulted in the high content of proteasomes. Another culprit may be activation of CP by membrane components (Arizti et al, 1993). its posttranslational modifications or a presence of CP distinctively decorated with activator modules (Hanna and Finley, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…From the position of the phosphorylated proteasome subunits on two-dimensional PAGE gels, in the present study, it is clear that C8 might be the single 30-kDa subunit recently reported to be phosphorylated in vitro by a casein kinase I1 activity found in purified human erythrocyte proteasome preparations 1371. Casein kinase 11 activity in purified rat liver proteasome preparations has been reported to phosphorylate both C8 and C9 in v i m [53]. The amino acid sequence of C8 but not that of C9 contains a number of putative casein kinase I1 phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…The protein levels of 26s proteinase/proteasome were approximately 1 : 2 as assessed by immunoblotting with antLC9 MCP257. in v i m [53]. The amino acid sequence of C8 but not that of C9 contains a number of putative casein kinase I1 phosphorylation sites.…”
Section: Substratementioning
confidence: 99%